A novel secure key-exchange protocol using biometrics of the sender and receiver. (November 2017) - Barman, Subhas; Chattopadhyay, Samiran; Samanta, Debasis; Panchal, Gaurang
Highlights: A session-based key exchange protocol is proposed using enrolled biometric data. Users' biometric data and the session key are protected from a number of attacks. Biometric data can be easily revoked and updated by an online mechanism. Biometrics of sender and receiver and their keys are combined to generate a locker. Error Correction codes and fuzzy commitment scheme are used for key regeneration. Graphical abstract: Abstract: Recently, biometric data have been integrated with cryptography to make stronger cryptographic systems called crypto-biometric systems (CBSs). In a CBS, cryptographic keys are linked with users' biometric data so that a large cryptographic key need not be memorized. In this paper, we introduce a key-exchange protocol using the biometric data of the sender and receiver. Users enroll their biometric data in a central server, and a communication session between enrolled users is established through the central server. A user generates a cryptographic key randomly and shares it with another user using a biometrics-based cryptographic construction. The cryptographic framework is constructed using the biometric data of two communicating users so that they may share a session key. In our protocol, the privacy of the biometric data is preserved for both the sender and the receiver.